An Intraday Pricing Model of Foreign Exchange Markets - Romeu, Rafael (IMF Working Papers; Working Paper ;, 2003)
Market makers learn about asset values as they set intraday prices and absorb portfolio flows. Absorbing these flows causes inventory imbalances. Previous work has argued that market makers change prices to manage incoming flows and offset inventory imbalances. This study argues that they have multiple instruments, or ways to manage inventory imbalances and learn about evolving asset values. Hence, they smooth inventory levels and update prior information about assets using multiple instruments. In ignoring other instruments, previous studies have ignored the information that these provide and overemphasize the role of price changes in inventory management. The model presented here provides new estimates of asymmetric information and inventory effects, the price impact of each instrument, the cost of liquidity, and the impact of an intervention on these costs.